Disclosure of tax incentives and the corporate liabilities in Brazilian public companies: a quantitative study. (2016) - Formigoni, Henrique; Segura, Liliane Cristina; Mantovani, Flavio Roberto; Carreira, Francisco Alegria; Abreu, Rute
This article aims to evaluate the effect of tax incentives on the liability level of firms listed in Brazilian Stock Exchange. Obtaining the tax incentives require many investments from the company. This paper contributes with the literature to identify if the companies that disclosed their fiscal incentives have any changes in their debt, because of these investments. The final sample was 382 firms, for the years 2010-2013, and with a total of 1, 528 observations. We used a regression model for the panel data in order to estimate the relation between liabilities and the fiscal incentives. The results show that encouraged firms have higher long-term debt and total debt than those who are not encouraged. In addition, the authors found a positive relationship between the assets of these companies and the tax incentive.